In nomine patris: Discursive strategies and ideology in the Cosa Nostra family discourse. (March 2017) - Poppi, Fabio Indìo Massimo; Di Piazza, Salvatore
Abstract: The article investigates how Cosa Nostra family discourse is characterized by a series of discursive strategies that give shape to specific ideological structures. By analysing a TV interview to the son of Bernardo Provenzano, boss of Cosa Nostra, it is possible to understand how the criminal values and practices are maintained and reproduced within the father–son relationship. Specifically, we show how the son justifies, legitimises or denies the criminal actions of his father. The ideology of Cosa Nostra seems to be based on the inter-generational cultural continuity of its members, on the family as main locus of adherence, reductionism of its mediatic image, amoralism as father–son relational constant and verticalism of the organisation as key framing device.